CONTINUING EDUCATION ACTIVITY - Daminov , A.T; Azamova , Nigina; Bekboyeva , Charos; Ismoilova , Husnora (Educational Research in Universal Sciences, 2024)
Goiter is an anatomical enlargement of the thyroid gland. It can be related with thyroid dysfunction or have normal thyroid function. This activity review the evaluation, and treatment of diffuse toxic goiter and explains the role of the interprofessional team in evaluating and patients with this condition. Objectives:Identify the etiology of diffuse toxic goiter medical conditions and emergencies.Outline the appropriate evaluation of diffuse toxic goiter.Review management options available for diffuse toxic goiter.Describe interprofessional team strategies for improving care coordination and communication to advance the care of diffuse toxic goiter and improve outcomes. Access free multiple choice questions on this topic. Introduction.Goiter simply refers to the enlargement of the thyroid gland. It can be due to various causes with the dietary iodine deficiency being the most common cause worldwide. In the United States, however, Graves disease and Hashimoto disease are the most commonly seen in clinical practice. The goiters have been classified in different categories, as per morphology (described as nodular versus diffuse), functional status (that could be hyperthyroid, hypothyroid, or euthyroid), the presence of malignancy, etc. By definition, a diffuse toxic goiter refers to a diffusely hyperplastic thyroid gland that is excessively overproducing the thyroid hormones.